Internationalization of the Indonesian Language: An Ontological, Epistemological, and Axiological Study - Nurul Lutfhi Aulia; Yaya Sunarya (al-Afkar, Journal For Islamic Studies, 2025)
History records that the Indonesian language has developed rapidly and has been used throughout the archipelago. In this era, the Indonesian nation must continue defending its existence. One way is by promoting the Indonesian language on the world stage. This research aims to delve into the ontology of the scope of the internationalization of the Indonesian language, formulate strategies for the internationalization of the Indonesian language epistemologically, and axiologically find the goals of the internationalization of the Indonesian language. A qualitative descriptive method is used in this research. The results describe that the Indonesian language is increasingly known worldwide through education, culture, bilateral and multilateral communication, and teaching that is very appealing to foreign speakers. Indonesian is now superior to Malay. The Indonesian language must maintain its existence to play a strong role in facing global dynamics and gradually become an internationally recognized. Therefore, Indonesian society needs to understand the urgency and existence of the internationalization of the Indonesian language by utilizing available technology and promoting BIPA programs.